Extraction and comparison of the total phenolic content from Malaysian grown kalanchoe pinnata (leaves and petioles) by using two different solvents ; Water and Ethanol / Fatimatuzzahraa Mohd Fadzel - Mohd Fadzel, Fatimatuzzahraa (Faculty of Applied Sciences, 2008)
Nowadays, even if technology has improved, humans still need the natural resources such as herbs which serve as a traditional remedies since so many years ago. There are many natural resources with high total phenolic content which are antioxidants constituents. From the previous research, antioxidants were found in tea leaves , garlic, broccoli and mangosteen However, there are no research of total phenolic content or antioxidant on a Malaysian-grown kalanchoe pinnata. The objective of this study is to extract and determine the total phenolic content in two parts of kalanchoe pinnata; leaves and petioles in two different solvents ; water and ethanol. The sample were extracted and Total phenolic content was determined by using Folin-Ciocalteu assay based on the Gallic acid standard calibration curve by using UV-VIS Spectrometer at 765nm. The Total phenolic content value was shown to be higher in leaf that were extracted by using ethanol with the value of 0.8816 mg/g GAE . As a conclusion, the content of total phenolic content in kalanchoe pinnata leaf are more effectively extracted by using ethanol than compared to water. COPYRIGHT ©